High-speed running type or stretching-type of hamstring injuries makes a difference to treatment and prognosis - Askling, C. M.; Malliaropoulos, N.; Karlsson, J. (British Journal of Sports Medicine, 2012)
Hamstring muscle strains are frequent in different sports and are the single most common injury in professional football. Several studies have indicated that hamstring strains are frequent in track and field as well, especially among sprinters and jumpers. The re-injury rate is high, which in most cases probably indicates inadequate rehabilitation programme and/or a premature return to sport.